2020
DOI: 10.1037/tps0000225
|View full text |Cite
|
Sign up to set email alerts
|

How the construct of metacognition has contributed to translational research in education, mental health, and beyond.

Abstract: Metacognition research dates back decades and remains a thriving field of scientific inquiry. From its inception, the construct was translational in nature, but only after years of research do we have the privilege of reflecting on the many basic and applied aspects of our knowledge about metacognition. Here, we discuss the metacognition literature from historical and translational-phase perspectives to support thinking about how to move this research from basic knowledge to real-world application. Translation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The positive association between grit and metacognition found in the present research can be attributed to the metacognitive processes in which individuals and teams engage in, during crucial decision making tasks ( McCarthy and Garavan, 2008 ). Metacognition has been studied in conjunction with theory of mind, social cognition and self-regulation ( Baker et al, 2020 ) and it has also been identified important to study job-seeking behaviours and job-search outcomes, as the process of seeking and finding jobs requires metacognitive skills, implying the ability to set goals, plan, develop and strategise their job search progress and job performance ( Mikulecky and Ehlinger, 1986 ; Turban et al, 2009 ; Kanar and Bouckenooghe, 2021 ). The other transpersonal capital of optimism also positively correlates with grit, consistent with previous studies ( Steinfort, 2015 ; Clement et al, 2020 ; Loftus et al, 2020 ; Oriol et al, 2020 ; Kim and Lee, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The positive association between grit and metacognition found in the present research can be attributed to the metacognitive processes in which individuals and teams engage in, during crucial decision making tasks ( McCarthy and Garavan, 2008 ). Metacognition has been studied in conjunction with theory of mind, social cognition and self-regulation ( Baker et al, 2020 ) and it has also been identified important to study job-seeking behaviours and job-search outcomes, as the process of seeking and finding jobs requires metacognitive skills, implying the ability to set goals, plan, develop and strategise their job search progress and job performance ( Mikulecky and Ehlinger, 1986 ; Turban et al, 2009 ; Kanar and Bouckenooghe, 2021 ). The other transpersonal capital of optimism also positively correlates with grit, consistent with previous studies ( Steinfort, 2015 ; Clement et al, 2020 ; Loftus et al, 2020 ; Oriol et al, 2020 ; Kim and Lee, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Meta-Performance Test takes the consensus built by the field of metacognition as a reference for the definition of its components. There is a relative consensus that metacognition consists basically of two major domains: (1) metacognitive knowledge and (2) control or regulation of cognition (e.g., Baker et al, 2020;Dent & Koenka, 2016;Ohtani & Hisasaka, 2018). The metacognitive knowledge about cognition (also called knowledge about cognition) refers to the individual's knowledge or beliefs about the variables that interact and can affect the course and results of cognitive tasks (Flavell, 1979).…”
Section: The Meta-performance Test's Rationale Conceptual Basismentioning
confidence: 99%
“…As a result, the research could be applied in multiple ways-to physical and mental health treatment, to the development of new psychological tools and measures, to organizational policies and practices, to educational practices, and to policy at the organizational, state, or federal levels. Some TPS issues focused on a psychological concept or theory, such as metacognition (Baker et al, 2020), incentives and motivation (Silverman et al, 2016), or positive psychology (Titova et al, 2018), with the articles showing how research in that area has been applied in multiple ways and settings, while other TPS issues kept the focus close in, looking at how psychological science can be advanced through improved research training (Fried et al, 2020), animal models (Threlkeld et al, 2019), and quantitative methods (Depaoli et al, 2018).…”
mentioning
confidence: 99%
“…Some TPS issues focused on a psychological concept or theory, such as metacognition (Baker et al, 2020), incentives and motivation (Silverman et al, 2016), or positive psychology (Titova et al, 2018), with the articles showing how research in that area has been applied in multiple ways and settings, while other TPS issues kept the focus close in, looking at how psychological science can be advanced through improved research training (Fried et al, 2020), animal models (Threlkeld et al, 2019), and quantitative methods (Depaoli et al, 2018).…”
mentioning
confidence: 99%